A National Survey of Clinical Hypnosis Views and Experiences of the Adult Population in the United States. Issue 4 (2nd October 2019) - Palsson, Olafur; Twist, Stefanie; Walker, Marcia
Abstract: A nationwide, demographically balanced Internet survey of 1000 adults (500 females, 500 males, mean age 49.5, range 18–88 years) was conducted to assess views and experiences of clinical hypnosis in the United States population. Participants were unaware when enrolling in the survey that hypnosis was the subject matter. Key findings included that most reported a positive (38.6%) or neutral (48.4%) view of clinical hypnosis, with only 12.8% expressing a negative view; 7.6% of respondents had undergone hypnosis treatment, and 63.1% reported some resulting benefit; 54.9% of individuals who had never undergone hypnosis treatment indicated that they would consider seeking such treatment; 45.6% of all respondents thought there was moderate or strong scientific evidence supporting hypnosis as a real phenomenon; 77.8% identified one or more areas where they thought clinical hypnosis had substantial practical utility, and 44.8% estimated themselves to be at least moderately hypnotizable.